Potentially functional polymorphisms in PAK1 are associated with risk of lung cancer in a Chinese population. (17th September 2015) - Zheng, Mingfeng; Liu, Jia; Zhu, Meng; Yin, Rong; Dai, Juncheng; Sun, Jie; Shen, Wei; Ji, Yong; Jin, Guangfu; Ma, Hongxia; Dong, Jing; Xu, Lin; et al.
Abstract : Potential functional polymorphisms in P21‐activated kinase 1 (PAK1) gene were associated with lung cancer risk in a Chinese population. A significant interaction between polymorphisms and smoking levels were detected on lung cancer risk. Abstract: P21‐activated kinase 1(PAK1) plays an important role in the regulation of cell morphogenesis, motility, mitosis, and angiogenesis and has been implicated with tumorigenesis and tumor progression. We hypothesized that functional polymorphisms in PAK1 gene may modify the risk of lung cancer. We screened four potentially functional polymorphisms (rs2154754, rs3015993, rs7109645, and rs2844337) in PAK1 gene and evaluated the association between the genetic variants and lung cancer risk in a case– control study including 1341 lung cancer cases and 1982 cancer‐free controls in a Chinese population. We found that variant allele of rs2154754 was significantly associated with a decreased risk of lung cancer (OR = 0.85, 95% CI: 0.77–0.95, P  = 0.004), meanwhile the result of rs3015993 was marginal (OR = 0.90, 95%CI: 0.81–1.00, P  = 0.044). After multiple comparisons, rs2154754 was still significantly associated with the lung cancer risk ( P  < 0.0125 for Bonferroni correction). We also detected a significant interaction between rs2154754 genotypes and smoking levels on lung cancer risk ( P  = 0.042). Combined analysis of these two polymorphisms showed a significant allele‐dosage association between the number of protective alleles and reduced risk of lung cancer ( P trend  = 0.008). These findings indicate that genetic variants in PAK1 gene may contribute to susceptibility to lung cancer in the Chinese population.